Resurgence initiation and subsolidus eruption of cold carapace of warm magma at Toba Caldera, Sumatra - Mucek, Adonara E.; Danišík, Martin; de Silva, Shanaka L.; Miggins, Daniel P.; Schmitt, Axel Karl; Pratomo, Indyo; Koppers, Anthony; Gillespie, Jack (Communications earth & environment, 2021)
Supervolcanoes like Toba Caldera, Sumatra, produce the largest eruptions on Earth. However, the magmatic conditions and processes during the period of recovery after catastrophic supereruptions, known as resurgence, are poorly understood. Here we use Bayesian statistical analysis and inverse thermal history modelling of feldspar argon-argon and zircon uranium-thorium/helium ages to investigate resurgence after the 74-thousand-year-old Youngest Toba Tuff eruption. We identify a discordance of up to around 13.6 thousand years between older feldspar and younger zircon ages. Our modelling suggests cold storage of feldspar antecrysts prior to eruption for a maximum duration of around 5 and 13 thousand years at between 280 °C and 500 °C. We propose that the solidified carapace of remnant magma after the Youngest Toba Tuff eruption erupted in a subsolidus state, without being thermally remobilized or rejuvenated. Our study indicates that resurgent uplift and volcanism initiated approximately 5 thousand years after the climactic caldera forming supereruption.